Nominal and positional perspectives on educational stratification in Israel. (March 2016) - Rotman, Assaf; Shavit, Yossi; Shalev, Michael
Highlights: Consequences of educational expansion on inequality of attainments are examined. Absolute and relative measures of educational attainments are compared. Inequality of educational opportunities tends to persist in absolute terms. Inequality increases when the changing value of education is accounted for. Abstract: This paper examines whether the rising accessibility of educational qualifications attenuates the association between social origin and educational attainment. Research is divided on the question of persistence of inequality of educational opportunities (IEO). Currently most studies on this issue focus on attainment of nominal levels of education and fail to acknowledge that educational expansion is accompanied by change in the value of qualifications and in their scarcity. This study employs measures of educational attainment that capture the changing scarcity and economic value of qualifications. Data from the 1995 and 2008 censuses in Israel are used to compare the association of socioeconomic origin with educational attainment between two birth cohorts. The results show that IEO tends to persist or decline, when attainment is measured in absolute terms, but tends to increase when relative measures of qualifications or measures representing their economic value are employed. The familiarity of better off parents with the school system and their awareness of changes in the value of qualifications are offered as a central factor that explains the findings.